Prospective audit to evaluate the potential of the coronial system to increase solid organ donation. Issue 7 (8th July 2016) - Twamley, Huw; Haigh, Andrew; Williment, Claire; Hudson, Cara; Whitney, Julie; Neuberger, James
Abstract : Objectives: Anecdotal evidence suggests that organ donation from deceased donors referred to the Coroner/Procurator Fiscal (PF) could be increased if all followed best practice. The aim of this prospective audit was to establish how referrals affected organ donation and to develop evidence-based guidelines to ensure that organ donation can be facilitated safely without interfering in the Coroner/PF's investigative process. Design: Prospective audit. Setting: All acute National Health Service Hospitals in the UK where deceased organ donation was considered. Participants: 1437 deceased patients who met the eligibility criteria for organ donation and were referred to Coroner/PF. Main outcome measures: Number of cases where permission for transplantation was given, number of organs where permission was refused and number of organs which might have been transplanted if all had followed best practice. Results: Full permission for organ retrieval was given in 87% cases and partial permission in 9%. However, if full permission had been given where no autopsy was performed or restrictions seemed unjustified, up to 77 organs (22 lungs, 22 kidneys, 9 pancreases, 9 livers, 8 hearts and 7 small bowels) could have been available for transplant. Conclusions: Coroners/PFs and their officers show strong support for transplantation but improvement in practice could result in a small but significant increase in life-saving and life-enhancing transplants.